Use of information and communication technologies (ICT) in physiotherapy teaching in Portugal - Alves Lopes, António (2022)
OBJECTIVE: This study aims to carry out a survey regarding the use of Information and Communication Technologies (ICT) in Physiotherapy teaching in Portugal, namely the characterization of the usage of the ICT by the institutions that offer the Physiotherapy course, as well as by Physiotherapy teachers and students. RELEVANCE: The European Region of the World Confederation for Physical Therapy refers in its document European Benchmark Statement that the Physiotherapist should have skills in the area of ICT, so that he/she is able to search for the required evidence to validate his/her practice, as well as managing the data and records stemming from his/her clinical practice. Therefore those skills should be developed during their basic training, and so should teachers be able to introduce the ICT in the teaching process, keeping in mind the institutional framework of this process. SAMPLE: The sample of teachers and students in the school year of 2003/2004 was taken from a population comprising a total of 16 institutions. MATERIAL AND METHODS: A questionnaire was especially set up and was validated by a panel of experts and by a pre-test. This questionnaire was subdivided into 6 dimensions (sample characterization, equipment characterization, usage characterization, attitudes and knowledge, barriers and necessities. STATISTICS: The procedures used were essentially descriptive statistics. RESULTS: Regarding accessing the Internet in the institution, 98% of the teachers and students refer to have access to Internet linked computers. When inquired about the usage of the computer for academic activities, 99% of the teachers and students answered affirmatively, of which 35% of the teachers use it more than 10 hours per week and 28% between 5 to 10 hours. As for the students, the percentage of weekly usage is of 42,6% between 0 and 3 hours and 36,7% between 3 and 5 hours. Furthermore 81% of the inquired teachers and 57,4% of the inquired students referred to fully agree regarding the importance of the usage of the ICT in school context. Although 84% of the inquired teachers reported to have knowledge in the area of the ICT, almost 51% pointed out the lack of specific training for integration/usage of the ICT as being the main barrier in the usage, then followed by the inexistence of strategies that facilitate the integration of the ICT in education/learning (44%). CONCLUSIONS: Through the analysis of the results of this study it is demonstrated that although the good accessibility to the ICT by teachers and students in their institutional and home environment, it is yet scarce due to the lack of specific training in this area. There seems to be the need to create institutional programs and projects that promote the usage of ICT by investing in the training of teachers and through the integration of those skills in the Physiotherapy course.